2016
DOI: 10.1016/j.jphysparis.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Co-adaptation of electric organ discharges and chirps in South American ghost knifefishes (Apteronotidae)

Abstract: Animal communication signals that simultaneously share the same sensory channel are likely to coevolve to maximize the transmission of each signal component. Weakly electric fish continuously produce a weakly electric field that functions in communication. Fish modulate the electric organ discharge (EOD) on short timescales to produce context-specific signals called chirps. EODs and chirps are simultaneously detected by electroreceptors and processed in the electrosensory system. We analyzed these signals, fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 55 publications
3
19
0
2
Order By: Relevance
“…Petzold et al (2016), found that the conspicuousness of chirps of different species was affected by parameters of both EODs and chirps. We hypothesized that EOD waveform and chirp parameters (FM and duration) might have co-evolved with each other to optimize the detection and/or discrimination of conspecific chirps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Petzold et al (2016), found that the conspicuousness of chirps of different species was affected by parameters of both EODs and chirps. We hypothesized that EOD waveform and chirp parameters (FM and duration) might have co-evolved with each other to optimize the detection and/or discrimination of conspecific chirps.…”
Section: Discussionmentioning
confidence: 99%
“…We tested two additional hypothesized relationships based on recent findings that EOD waveform influences the conspicuousness of chirps (Petzold et al, 2016). Specifically, we asked whether EOD waveform complexity (F2-F1) was associated with chirp FM or chirp duration to test the hypothesis that EOD waveform complexity co-evolves with chirp parameters to maximize their conspicuousness.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas rises seem to be highly conserved between species, chirps and EOD waveforms appear to be evolutionarily labile (Turner et al, 2007), and thus chirps are potential additional cues for species identification (Fugère and Krahe, 2010). The different types of chirps and EOD waveforms result in various degrees of conspicuousness of the resulting signals (Petzold et al, 2016) that may translate into discriminability by the electrosensory system. Chirps have also been suggested to aid disambiguation of the sign of high-frequency beats (Walz et al, 2014).…”
Section: Species-specific Eod Frequenciesmentioning
confidence: 99%
“…Identity can be determined from the EOD pattern (Fig 2a): depending on the species, EOD frequency, shape or pulse pattern can be used to identify conspecifics from individuals of another species (Zupanc, Sîrbulescu, Nichols, & Ilies, 2006) or even differentiate amongst conspecifics (Zakon, Oestreich, Tallarovic, & Triefenbach, 2002). In wave type species, the EOD frequency (and possibly shape; Kolodziejski, Sanford, & Smith, 2007;Petzold, Marsat, & Smith, 2016) is perceived indirectly.…”
Section: Behavior and Signal Propertiesmentioning
confidence: 99%